Geomorphic index alterations and socioeconomic implications: A case study of a Coastal River system in Bangladesh - Sukhen Goswami; Md. Masum Billah; Md Sabbir Hossen; Mehedi Hasan Ovi; Shacin Chandra Saha; Mir Md. Tasnim Alam; Probir Kumar Bhowmik; Atikul Haque Farazi; Md. Ashraful Islam; Dhiman Kumer Roy (Progress in Disaster Science)
Riverbank erosion, driven by natural processes and human activities, poses significant socio-environmental challenges in Bangladesh. This study investigated the geomorphic evolution and socioeconomic impacts of riverbank erosion along the Sandhya River in Babuganj Upazila, Barishal, Bangladesh. The primary aim was to assess how natural processes and human interventions, such as sand mining and infrastructure development, have altered the river morphology and affected local communities. Landsat imagery from 1980 to 2023, with a 10-year interval, was analyzed to assess key geomorphic indices—sinuosity, channel width, widening rate, and migration rate using remote sensing, geographic information systems (GIS), and field surveys. The results indicate significant geomorphic transformation, with sinuosity varying between 1.01 and 2.08, with a post-2000 increase in channel widening (up to 27 m/year) linked to intensified sand mining and brickfield expansion. Mid-channel bar formation, absent before 2000, reached 4.0 km2 by 2023, affecting flow patterns. The widening rate shifted from a maximum of 19 m/year (1980–2000, pre-sand mining) to 27 m/year (2000–2023, post-sand mining), with a peak near Doarika Bridge, which increased the vulnerability of the Barishal Airport area, averaging 3.65 m/year. Socioeconomic surveys (n = 154) reveal severe livelihood disruption: 65 % of lost land was agricultural, 73 % of affected households migrated to urban centers, and 45 % fell into debt. The most affected areas were Dehergati, Rahamatpur, Rakudia, and Kedarpur, emphasizing the need for capacity building. The study concludes that integrated geomorphic restoration and community resilience planning are urgently needed to address erosion-driven displacement and economic vulnerability in the region.